Determination of Amoxicillin in Pharmaceutical preparations by spectrophotometric and flow Injection – activated chemiluminescence methods - K.Ahmed, Abdul Majeed; J. Shakkor, Shahla (Tikrit Journal of Pharmaceutical Sciences, 2023)
This investigation involves development of a simple pectrophotometric method and a flow injection – activated chemiluminescence (FIA-Cl) for the determination of amoxicillin (Amox.) in pharmaceutical formulations. Spectrophotometric method was based on the oxidation of the (Amox.) with alkaline potassium permanganate, the reaction was followed spectrometrically by measuring the absorbance of (Amox.) at 600 nm. The reaction time of oxidation at (20 min) method is adopted for determining the drug concentration. The calibration graph was linear in the range of (5-50)µg.ml-1 with a correlation coefficient of (0.9995), detection limit of (4.76) µg.ml-1, molar absorption coefficient is 2557.8 L/mol.cm and a relative standard deviation RSD% of (1.84%). The method of FIA-CL was based on the activation of luminol – cobalt – H2O2 chemiluminescence by (Amox.). The linearity is (8-32) µg.ml-1 with detection limit of (6.2)µg.ml-1, and correlation coefficient was (0.9998 ) n=6 and the relative standard deviation was(1.48%). The two methods were applied successfully to determine the content of (Amox.) in pharmaceutical preparations with a recovery of 98.9% .